1978
DOI: 10.4039/ent110143-2
|View full text |Cite
|
Sign up to set email alerts
|

REVISION OF THE NEARCTIC WOLF SPIDER GENUSSCHIZOCOSA(ARANEIDA: LYCOSIDAE)

Abstract: Schizocosa Chamberlin, 1904, with type-species Lycosa ocreata Hentz, 1844, comprises 20 species occurring in southern Canada, the U.S.A., and Mexico: S. ocreata (= Lycosa charonoides Montgomery, 1902, SYN. N.); S. crassipes (Walckenaer, 1837); S. floridana Bryant, 1934; S. saltatrix (Hentz, 1844); S. humilis (Banks, 1892) (= Lycosa episima Chamberlin, 1924, SYN. N.); S. duplex Chamberlin, 1925; S. salsa Barnes, 1953; S. bilineata (Emerton, 1885); S. segregata Gertsch and Wallace, 1937; S. aulonia Dondale, 1969… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…This seems unlikely for several reasons. First, given the high level of sexual size dimorphism found in this species (male = 5.74-7.4 mm, female = 7.75-12.8 mm;Dondale and Redner 1978), females can almost certainly dislodge a male attempting a mount if they so choose. This is supported by a large number of observations of females dislodging males after a successful male mount (Hebets EA, Rundus AS, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…This seems unlikely for several reasons. First, given the high level of sexual size dimorphism found in this species (male = 5.74-7.4 mm, female = 7.75-12.8 mm;Dondale and Redner 1978), females can almost certainly dislodge a male attempting a mount if they so choose. This is supported by a large number of observations of females dislodging males after a successful male mount (Hebets EA, Rundus AS, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…Wolf spiders of the genus Schizocosa are abundant members of forest litter communities in the eastern United States (Dondale and Redner 1978;Stratton 1991). Adult females weigh about 70 mg. Spiders in this study came from a mixed mesophytic forest in Madison Co., Ky., where two cryptic Schizocosa species occur (Wagner and Wise 1997).…”
Section: Study Speciesmentioning
confidence: 99%
“…Heimer & Nentwig 1991) and some Nearctic and African genera have been recently revised (e.g. Alderweireldt 1991Alderweireldt , 1999Dondale & Redner 1978, 1979, 1983a, 1983bRussell-Smith 1982), a large number of the 2245 lycosid species (Platnick 2001) would seem to be misplaced. For example, a revision of the New Zealand lycosid fauna (Vink 2002) found that all but one described species were incorrectly placed in mostly Northern Hemisphere genera.…”
mentioning
confidence: 99%